(untitled) (Medicine Today, 2022)
Introduction: Chronic osteomyelitis is a surgical disease that can require significant dedication from both patient and surgeon to eradicate. Treatment requires isolation of pathogen, significant debridement for removal of all infective and necrotic material, then bony and soft tissue reconstruction. Objective: We shall try to highlight the option of management of a pan-Diaphyseal osteomyelitis of a children in the new era of osteosynthesis by Ilizarov. Discussion: A two years old baby presented to us with the H/O chronic discharging sinus and arm sling for around 3 months. After clinical history taking and examination, radiography and pus testing (C/S) and sequestrum and pathological fracture was the identifying points we took the plan for exploration curettage and drainage. Finally we fix the arm by Ilizarov osteosynthesis for more than 3 months. The wound healed and osteomyelitis resolved. Conclusion: Use of Ilizarov osteosynthesis for fixation and wire tension effect to resolve the infection1,2 Medicine Today 2022 Vol.34(2): 157-158